Early coronary angiography in patients resuscitated from out of hospital cardiac arrest without ST-segment elevation: A systematic review and meta-analysis - Khan, Muhammad Shahzeb; Shah, Sayed Mustafa Mahmood; Mubashir, Ayesha; Khan, Abdur Rahman; Fatima, Kaneez; Schenone, Aldo L.; Khosa, Faisal; Samady, Habib; Menon, Venu (Resuscitation, 2017)
A meta-analysis of published studies was performed to determine the impact of performing early versus delayed or no coronary angiography in patients without ST-segment elevation myocardial infarction following out of hospital cardiac arrest. A structured search was conducted using Medline, Embase and Ovid by two independent investigators using a variety of keywords. The primary outcome was short term (at discharge) and long term (at 6–14 months follow-up) mortality whereas the secondary end-point was good neurological outcome (defined as a Cerebral Performance Category Score of 1 or 2), at discharge and follow up. Random-effects model was utilized to pool the data, whilst publication bias was assessed using funnel plot. A total of 8 studies (7 observational studies and 1 randomized control trial) were identified and incorporated into the meta-analysis. The use of early angiography was associated with decreased short term (OR=0.46, 95% CI=0.36–0.56, P<0.001) and long term (OR=0.59, 95%CI=0.44–0.74, P<0.001) mortality. Early angiography was also shown to be associated with improved neurological outcomes on discharge (OR=2.00, 95% CI=1.50–2.49, P<0.001) as well as on follow-up (OR=1.48, 95% CI=1.06–1.90, P<0.001). The results of our meta-analysis support the use of early coronary angiography in out of hospital cardiac-arrest patients presenting without ST-segment elevation on the post-resuscitation electrocardiogram. However, given the low level of evidence of available studies, future guideline changes should be directed by the results of large-scale randomized clinical trials on the subject matter.